Mind-body training for performing under pressure - Thornton, L. (Olympic & Paralympic Coach, 2014)
This article will elaborate on the application of training in preparation for performing at big events, such as the Olympic Games. Athletes often experience pressure as they compete in qualifiers and sanctioned events leading up to, and at the Olympic Trials and Games. One interpretation of pressure is a change in the perceived importance of the outcome of an event. The key in that phrase is the change in the perception. This change may lead athletes to modify or introduce new thoughts and emotions (and experience different physiological reactions) into their precompetitive routine. The downstream effects may be noticed first, for example in a pounding heartbeat, and the upstream effects may follow, with the athlete making sense of what the change in the heartbeat might mean - nervous, excited, ready? More thoughts flow from this interpretation, and part of psychophysiology training includes better understanding the effects of thoughts and emotions on the body, and to practice the redirection and/or regulation of both. Upstream changes, namely those that originate from the brain and the mind, can flow downstream and the athlete can experience changes in physiology from thoughts or emotions. With biofeedback and neurofeedback technology, we can measure this interaction between the mind and body, with the goal of creating awareness and teaching athletes to more effectively regulate the two.